Making Fiscal Decentralization Work : Cross-Country Experiences - Fedelino, Annalisa (Occasional Papers; Occasional Paper, 2010)
The question of what makes fiscal decentralization work is faced by many policymakers around the world. This book draws on both the relevant literature and policy and technical advice provided by the IMF to a wide range of member countries, and discusses the key factors that help make decentralization sustainable, efficient, and equitable from a macroeconomic perspective. It focuses on institutional reforms (in the revenue and expenditure assignments to different levels of government, the design of intergovernmental transfers, and public financial management systems) that are suited to different countries circumstances, and their appropriate sequencing.